2006
DOI: 10.2106/jbjs.d.02533
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and Functional Outcome Following Sacrectomy for Sacral Chordoma

Abstract: Therapeutic Level IV. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
92
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 28 publications
10
92
1
4
Order By: Relevance
“…Thus, the expected toxicity after radical resection would have been a complete urinary and bowel incontinence in at least 80% of the patients [20,21]. Furthermore chronic neuropathic pain, wound complications and walking difficulties are also possible side effects of sacrectomy [30,31]. Against this background, the published side effects after hypofractionated carbon ion therapy should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expected toxicity after radical resection would have been a complete urinary and bowel incontinence in at least 80% of the patients [20,21]. Furthermore chronic neuropathic pain, wound complications and walking difficulties are also possible side effects of sacrectomy [30,31]. Against this background, the published side effects after hypofractionated carbon ion therapy should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that chances to obtain an R0 resection are higher for patients who have an accurate preoperative diagnosis and who undergo an aggressive multidisciplinary treatment rather than for patients who have been misdiagnosed and are in need of secondary surgery [3, 4, 11, 13]. The quality of surgical margins at initial surgery is the primary prognostic factor for LR [7, 11, 12, 17, 18, 19], with the 10-year OS rates ranging between 30% and 65% depending on the surgical margins [5, 7, 8, 9, 10, 11, 12]. A review of the recent literature shows LR rates ranging between 0% and 60% for wide margins, between 31% and 71% for marginal margins, and between 67% and 100% for intralesional resection margins (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Distant disease is less frequent (20%-40%), but metastases to the bone, lung, liver, lymph-nodes and skin have been described [3, 4, 5, 6, 7]. The 10-year overall survival (OS) rate ranges from 30% to 65% [5, 7, 8, 9, 10, 11, 12]. Radical surgery is the only hope for cure as no chemotherapy has been demonstrated to be effective against a chordoma, and radiotherapy is only marginally effective [5, 7, 9, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In adult cases, the clinical course generally shows indolent progression (1,2,7). Certain studies have reported that the local recurrence rates in adult cases were 33–71% (8,9) and Hulen et al (10) identified that following a surgical procedure the mean time of first recurrence was 29 months (range, 12–66 months) and the mean time of metastases was 50 months (range, 16–122 months). In addition, previous studies demonstrated that the five- and 10-year overall survival rates of chordoma patients were 74–83 and 50–56%, respectively (8,11,12).…”
Section: Introductionmentioning
confidence: 99%